Islamic principles on sustainable land use planning and development - Maidin, Ainul Jaria (Routledge, 2011)
Rapid development globally has caused various environmental problems and impacted adversely on the world's natural resources. The United Nations promoted the concept of sustainable development to overcome environmental degradation arising from poorly planned development activities and exploitation of natural resources. However, the not much progress has been achieved in terms of overcoming environmental problems globally despite committing the efforts and resources. The Qur'an has addressed the need to protect the environment and man is prevented from destroying the earth's resources. This article explores the basic principles governing land use planning and environmental protection derived and practised by the Muslim Jurists as provided by Shari'ah (Islamic Law) and its relevance in achieving sustainable development goals. Manifestation of religious values in the land use planning system is examined via introduction and implementation of the Total Planning and Development Doctrine as a planning guideline in Malaysia as a case study.